2020
DOI: 10.3389/fcell.2019.00347
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids of Seminal Plasma Associated With Freezability of Bull Sperm

Abstract: Sperm cryopreservation is an important technique for fertility management, but postthaw viability of sperm differs among breeding bulls. With metabolites being the end products of various metabolic pathways, the contributions of seminal plasma metabolites to sperm cryopreservation are still unknown. These gaps in the knowledge base are concerning because they prevent advances in the fundamental science of cryobiology and improvement of bull fertility. The objective of this study was to test the hypothesis that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 66 publications
1
40
1
3
Order By: Relevance
“…The current knowledge in humans about the different epigenetic signals in sperm that are responsive to environment and evidence of sperm-borne epigenetic factors is well-reviewed in Donkin and Barres ( 2018 ). In cattle, studies using sperm samples from low and high fertility bulls have suggested various sperm factors associated with bull fertility, including sperm proteomics, gene expression, sperm protamine status, macromolecules, metabolomics, superoxide dismutase, and amino acids of seminal plasma (Peddinti et al, 2008 ; Feugang et al, 2010 ; Govindaraju et al, 2012a ; De Oliveira et al, 2013 ; Dogan et al, 2015 ; Grant et al, 2015 ; Kaya and Memili, 2016 ; Kutchy et al, 2017 , 2019 ; Velho et al, 2018 , 2019 ; Viana et al, 2018 ; Menezes et al, 2019 ; Ugur et al, 2019 ; Memili et al, 2020 ).…”
Section: Epigenetic Determinants Of Gamete and Embryo Viabilitymentioning
confidence: 99%
“…The current knowledge in humans about the different epigenetic signals in sperm that are responsive to environment and evidence of sperm-borne epigenetic factors is well-reviewed in Donkin and Barres ( 2018 ). In cattle, studies using sperm samples from low and high fertility bulls have suggested various sperm factors associated with bull fertility, including sperm proteomics, gene expression, sperm protamine status, macromolecules, metabolomics, superoxide dismutase, and amino acids of seminal plasma (Peddinti et al, 2008 ; Feugang et al, 2010 ; Govindaraju et al, 2012a ; De Oliveira et al, 2013 ; Dogan et al, 2015 ; Grant et al, 2015 ; Kaya and Memili, 2016 ; Kutchy et al, 2017 , 2019 ; Velho et al, 2018 , 2019 ; Viana et al, 2018 ; Menezes et al, 2019 ; Ugur et al, 2019 ; Memili et al, 2020 ).…”
Section: Epigenetic Determinants Of Gamete and Embryo Viabilitymentioning
confidence: 99%
“…Sperm freezability was determined according to methods that have been previously described by other researchers 12 . Briefly, bulls (Alta Genetics, Watertown, WI, USA) were selected based on post-thaw viability data that were collected from 2008 to 2016.…”
Section: Sperm Freezability Determination and Experimental Designmentioning
confidence: 99%
“…In seminal plasma, the components generally consist of proteins, ions, and metabolites like nucleosides, lipids, monosaccharides, amino acids, minerals, electrolytes, and also steroid hormones 9,10 . Previous studies have proved that seminal plasma contributes a signi cant role in regulation of sperm motility and fertilization [11][12][13][14][15] . Seminal plasma provides metabolic support, and it has a complicated and not well-understood effect on the physiological role of sperm.…”
Section: Introductionmentioning
confidence: 99%